Caregiver Reactions to Aggressive Behaviors in Persons With Dementia in a Diverse, Community-Dwelling Sample. (January 2020) - Hansen, Bryan R.; Hodgson, Nancy A.; Budhathoki, Chakra; Gitlin, Laura N.
Purpose: To describe caregiver challenges with and confidence managing three aggressive behavior types in persons with dementia: verbal aggression, destroying property, and threatening to hurt others.Design and Method: Secondary analysis of baseline data from the 2001-2004 Resources for Enhancing Alzheimer's Caregiver Health II (REACH II) initiative.Results: One or more aggressive behaviors within 1 week were reported by more than a third of caregivers, with most expressing upset but fewer expressing confidence managing the behaviors. Caregiver distress and confidence differed by race/ethnicity in response to verbal aggression, with more White/Caucasian caregivers expressing upset than Hispanic/Latinos or Black/African Americans. Fewer Hispanic/Latinos expressed confidence managing verbal aggression, compared with White/Caucasians or Black/African Americans.Discussion: Aggressive behaviors challenge caregivers, with reactions varying by behavior type and race/ethnicity. Cultural and contextual factors suggest the need to tailor interventions, especially skill-building interventions that increase confidence managing aggressive behaviors while decreasing upset.